2019
DOI: 10.1042/bsr20191692
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction between β-catenin and sorting nexin 27: contribution of the type I PDZ-binding motif to Wnt signaling

Abstract: Background: Sorting Nexin 27 (SNX27) is a 62-kDa protein localized to early endosomes and known to regulate the intracellular trafficking of ion channels and receptors. In addition to a PX domain common among all of the sorting nexin family, SNX27 is the only sorting family member that contains a PDZ domain. To identify novel SNX27–PDZ binding partners, we performed a proteomic screen in mouse principal kidney cortical collecting duct cells (mpkCCD) using a GST-SNX27 fusion construct as bait. We found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, yeast two-hybrid assays demonstrated the direct interactions of β-catenin, JAM-B, and filamin A with harmonin (data not shown). β-catenin presumably bind to the PDZ1 and PDZ3 domains of harmonin via a C -terminal type-I PDZ binding motif (DTDL) (DuChez et al, 2019). In contrast, JAM-B contains a canonical type II PDZ targeting motif (FLV) at position 298-300 of its C -terminus, which is likely responsible for binding to harmonin (Ebnet et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, yeast two-hybrid assays demonstrated the direct interactions of β-catenin, JAM-B, and filamin A with harmonin (data not shown). β-catenin presumably bind to the PDZ1 and PDZ3 domains of harmonin via a C -terminal type-I PDZ binding motif (DTDL) (DuChez et al, 2019). In contrast, JAM-B contains a canonical type II PDZ targeting motif (FLV) at position 298-300 of its C -terminus, which is likely responsible for binding to harmonin (Ebnet et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Of notice, Snx27 was identified as an alternative-splicing product of Mrt1 (methamphetamine responsive transcript 1) gene that was developmentally regulated and drug-inducible [141]. More recently, a study highlighted how SNX27 interaction with β-catenin, through its PDZ domain, can possibly shape Wnt signaling and, hence, embryonic developmental processes [164]. Furthermore, SNX27 associates with epilepsy [146] and patients with SNX27 variants display seizures, developmental delay, behavioral disturbance, and subcortical brain abnormalities [152].…”
Section: Px-only Subfamily Work By Our Group and By Harterink Supports Snx3 Involvement In Development Through Its Role Inmentioning
confidence: 99%
“…We show this with the present interaction assays in mammalian cells and in situ by PLAs, confirming previous in vitro data ( Johnston et al, 2004 ; Nagel-Wolfrum et al, 2022 ). The binary interaction of harmonin and β -catenin is mediated by binding of the C-terminal tail of β -catenin with its type I PBM (DTDL) ( DuChez et al, 2019 ) to PDZ domains 1 and 3 on harmonin, with a slight preference for PDZ3 ( Nagel-Wolfrum et al, 2022 ). Binding of the C-terminal PBM of β -catenin to PDZ domains has been previously described for interactions with other PDZ domain-containing proteins such as MAGI-1 and LIN7 ( Dobrosotskaya and James, 2000 ; Perego et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have further indicated that PBM-mediated interactions of β -catenin are also essential for its role as a coactivator in the cWnt pathway ( DuChez et al, 2019 ). The interaction of the small PDZ protein EBP50 with the PBM of β -catenin potentiates its transcriptional activity in liver cancer cells ( Shibata et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%